Basal and induced granulopoiesis in outbred, F1 hybrid and inbred mice: can inbreeding depression influence the experimental practice? - Hofer, Michal; Pospísil, Milan; Dusek, Ladislav; Holá, Jirina; Hoferová, Zuzana; Weiterová, Lenka (Experimental biology and medicine (Maywood, N.J.), 2010)
In this study we examined differences in selected indices of granulopoiesis in outbred, F(1) hybrid and inbred mouse strains. Specifically, serum granulocyte colony-stimulating factor (G-CSF) levels, numbers of marrow granulocyte-macrophage progenitor cells and morphologically recognizable proliferative marrow granulocytic precursor cells were evaluated. These parameters were determined in untreated controls, and in mice exposed either to a non-specific stimulus (injection of saline) or to a granulopoiesis-enhancing stimulus (administration of a cyclooxygenase-2 inhibitor, meloxicam). Lower levels of G-CSF were detectable in the outbred ICR mice, which also demonstrated an enhanced response to both types of the stimuli. Considering the fact that outbred mice are closer to natural mammalian populations, including human ones, the possibility of using outbred mice, instead of the often used inbred strains, for experiments evaluating the effects of pharmacological interventions on hematopoiesis should be investigated.
Keywords: Cyclooxygenase Inhibitors; Meloxicam; Sodium Chloride; mužské pohlaví; Granulocytes; injekce intraperitoneální; Inbreeding; Mice; Cell Proliferation; Mice, Inbred Strains; inbreeding; meloxikam; inbrední kmeny myší; granulocyty; buňky kostní dřeně; Myelopoiesis; faktor stimulující kolonie granulocytů; myelopoéza; Injections, Intraperitoneal; Thiazoles; zvířata; Humans; Bone Marrow Cells; Thiazines; thiazoly; Hybridization, Genetic; chlorid sodný; hybridizace genetická; myši; proliferace buněk; thiaziny; Granulocyte Colony-Stimulating Factor; progenitory granulocytů a makrofágů; inhibitory cyklooxygenasy; Granulocyte-Macrophage Progenitor Cells; faktor stimulující granulocyto-makrofágové kolonie; Granulocyte-Macrophage Colony-Stimulating Factor; lidé; Male; Animals